PEMBERDAYAAN USAHA RUMAH TANGGA OLAHAN BUAH SALAK SRADHA DI KABUPATEN KARANGASEM BALI - Telagawathi, Ni Luh Sayang (JURNAL WIDYA LAKSANA, 2017)
This empowerment program aims to improve the productivity of the products produced from the fruits of salak fruit, expand the reach of marketing and improve the understanding of partners about business planning and business management. These objectives are achieved through mentoring and training of business management of salak fruit processing industry, provision of adequate production equipment, marketing website creation and facilitating business group with capital institution. Besides famous as an agro-tourism area of Salak plantation, Sibetan Village has the potential of Small and Medium Enterprises in processing the salak fruit into dodol, pia, dates, crackers, syrup and wine. However, the management is still based on the household industry with limited capital and production, the production process is still simple, the packaging (packing) is sober, and marketing is still limited in District Bebandem and Kabupaten Karangasem. That's why this IbM program designed activities for two groups of salak processed household industries namely Salak Sradha Group in Telaga Village. Both groups are growing and need assistance in developing their business. The method of implementation to achieve this goal is to provide website creation assistance to facilitate the reach of marketing, supply of production equipment, facilitate business groups in gaining access to capital as well as assistance and training of business management planning and management. Keywords: fruit processing, production, marketing, packaging, business management